The Effects of Interprofessional Pediatric End-of-Life Simulation on Communication and Role Understanding in Health Professions Students. Issue 6 (November 2018) - Stout-Aguilar, Jacqueline; Pittman, Alison; Bentley, Regina; Livingston, Jerry; Watzak, Bree
Abstract : Abstract: The purpose of this study was to analyze the impact of interprofessional pediatric end-of life simulations for health professions students. A quasiexperimental design was used with three TeamSTEPPS® tools. Forty-one students were enrolled (nursing = 20, medicine = 10, pharmacy = 10, public health = 1). TeamSTEPPS 2.0 Teamwork Attitudes Questionnaire and Teamwork Perceptions Questionnaire analysis indicated a significant difference in mean pretest and posttest scores ( p = .015 and p = .028, respectively). The Team Performance Observation Tool indicated statistical significance between simulations ( p < .001, df = 18, r = .8). Simulations were significantly related to an increase in faculty observation scores, TeamSTEPPS 2.0 Teamwork Attitudes Questionnaire pre-post scores, and TeamSTEPPS 2.0 Teamwork Perceptions Questionnaire pre-post scores.